Metal surface long-acting rust transforming agent

By using a long-acting rust converter containing tannin, gallic acid and salicylic acid on the steel structure of marine buildings, the problem of insufficient effect of existing anti-rust conversion agents in marine environments is solved, and efficient and long-term corrosion resistance is achieved, which significantly saves maintenance costs.

CN119615139APending Publication Date: 2025-03-14QINGDAO HIGHFLY SAFETY TECH CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411908516.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing anti-rust rust-turning agents have high toxicity, poor construction economy, poor permeability and average protection against microbial corrosion, making it difficult to effectively prevent corrosion of marine building steel structures.

Method used

A metal surface long-acting rust conversion agent is provided, which contains 30% to 50% carrier oil, 1% to 4% permeability stabilizer, 6% to 10% sustained release carrier, 3% to 5% sterilizer, 1% to 2% antioxidant, 2% to 6% thixotropic agent, 10% to 20% tannic acid, 9% to 15% salicylic acid, 6% to 20% gallic acid, and through chelation, a dense complex layer is formed to prevent the infiltration of corrosive media.

Benefits of technology

This converter can form an efficient conversion film, and the long-term anti-corrosion effect can reach more than 20 years, reducing maintenance frequency, saving resources, manpower and material resources, and having significant economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615139A_ABST
    Figure CN119615139A_ABST
Patent Text Reader

Abstract

The invention provides a long-acting rust converting agent for metal surfaces, and relates to the technical field of marine metal surface rust prevention and conversion, tannic acid, gallic acid and salicylic acid are matched with each other and can form a firm complex layer with formed metal oxide or metal through chelation, and the metal surface rust conversion effect is improved. The synergistic effect of the tannic acid corrosion inhibitor, the gallic acid corrosion inhibitor and the salicylic acid corrosion inhibitor enhances the exertion of the synergistic migration protection effect, a relatively compact and smooth conversion film can be formed on the rusted metal surface, the formed conversion film can effectively prevent a corrosion medium from permeating into the metal surface to make contact with the metal, and the metal corrosion inhibitor is suitable for steel structures, especially suitable for steel structure connecting parts and has good corrosion resistance and corrosion resistance. The rust remover has the advantages that the rust remover is good in permeability and high in rust conversion efficiency, harmful rust can be converted into a protective layer beneficial to corrosion prevention, effective protection is provided for a metal matrix, the corrosion prevention effect can reach 20 years or above, frequent maintenance is omitted, resources, manpower and material resources are saved, and remarkable economic benefits are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field related to rust prevention and rust conversion on marine metal surfaces, and in particular to a long-acting rust conversion agent for metal surfaces. Background Art

[0002] Marine building steel structure refers to large structures built in marine environment using steel as the main building material, such as offshore platforms, cross-sea bridges, offshore wind power generation facilities, etc. Among them, marine building steel structure has the characteristics of light weight, high strength, good plasticity, etc. It can be designed into various complex shapes and structures according to the actual environment and work requirements, and withstand various complex loads in the marine environment (such as waves, tides, storms, etc.); at the same time, compared with traditional building materials, it is easy to process and install, which can greatly shorten the construction period of marine buildings, and thus is widely used in marine buildings.

[0003] The corrosion factors of marine steel structures in the marine environment are complex and diverse, mainly including chloride ions in seawater, salt in the marine atmosphere, microorganisms, acid rain, direct sunlight, and temperature changes between day and night. These factors will cause different degrees of corrosion of marine steel structures, which will affect the safety and service life of marine steel structures. Among them, seawater contains a large amount of chloride ions, which will react with iron oxide on the surface of marine steel structures to form soluble chlorides, accelerating the corrosion of marine steel structures. At the same time, the marine atmospheric environment is characterized by high salinity and high humidity, which will cause a layer of water film to form on the surface of the steel structure, providing a basic environment for electrochemical corrosion, and will also accelerate the corrosion of marine steel structures; especially in projects such as marine wind power generation, marine steel structures are exposed to the marine environment for a long time, and the corrosion problem is prominent. Microbial corrosion of marine steel structures, specifically various microorganisms in the marine environment, will adhere to the surface of the steel structure and produce acidic substances to corrode the marine steel structure; microbial corrosion usually causes small pore-shaped corrosion pits on the surface of marine steel structures, seriously affecting their strength and stability, and further aggravating the electrochemical corrosion of marine steel structures. Furthermore, acid rain, direct sunlight, and temperature changes between day and night will also aggravate the corrosion of marine steel structures. Compared with non-marine environments, the corrosion rate of steel structures in marine environments is several times that of non-marine environments. The corrosion inhibition and maintenance of marine steel structures requires a lot of manpower and material resources.

[0004] The most economical, effective and simplest way to prevent corrosion on the surface of marine steel structures is to apply an anti-corrosion coating on the surface. In order to enhance the performance and effect of anti-corrosion, it is necessary to thoroughly remove the rust on the substrate, and the steel surface should reveal a metallic luster. The widely used rust removal methods include mechanical methods, sandblasting, flame and chemical methods, but these methods have defects such as high labor intensity, low labor efficiency, high cost, environmental pollution, and health hazards to construction personnel. In particular, in the in-service engineering structure facilities, the components are complex and the environment is special, and the construction difficulty of conventional rust removal methods is relatively large. Therefore, in order to reduce labor intensity, enhance and improve the anti-corrosion effect, enhance the adhesion of the coating on the surface of the steel substrate, save resources, and achieve environmental protection, high efficiency, energy saving, and low surface treatment, it is urgent to provide a technology that can directly convert rust into a steel protective film, and then the anti-rust coating can be directly applied to the rusty metal surface to stabilize, passivate or convert the rusted surface, and convert the rust into a stable and harmless substance, without strict rust removal and surface treatment, low production cost, high rust conversion rate, and high anti-corrosion performance. Summary of the invention

[0005] The present invention aims at the shortcomings of existing rust-proof and rust-converting agents, such as high toxicity, poor construction economy, poor permeability and general protection effect against microbial corrosion, and provides a long-acting rust conversion agent for metal surfaces. The agent is suitable for steel structures, especially for steel structure connection parts, has good permeability and high rust conversion efficiency, can form a relatively dense and smooth conversion film, and the formed conversion film can effectively prevent corrosive media from penetrating into and contacting the metal, can convert harmful rust into a protective layer that is beneficial to corrosion prevention, and provide effective protection for the metal substrate. The anti-corrosion effect can reach more than 20 years, eliminating the need for more frequent maintenance, saving resources and manpower and material resources, and having significant economic benefits.

[0006] On the one hand, the present invention provides a long-acting rust conversion agent for metal surface, comprising 30% to 50% by mass of carrier oil, 1% to 4% by mass of osmotic stabilizer, 6% to 10% by mass of slow-release carrier, 3% to 5% by mass of sterilizer, 1% to 2% by mass of antioxidant, 2% to 6% by mass of thixotropic agent, 10% to 20% by mass of tannic acid, 9% to 15% by mass of salicylic acid, and 6% to 20% by mass of gallic acid, wherein the total mass percentage of tannic acid, salicylic acid and gallic acid contained in the long-acting rust conversion agent for metal surface is 25% to 50%.

[0007] Optionally, the mass percentage of tannic acid contained in the long-acting rust conversion agent for metal surface is 12%~16%, the mass percentage of salicylic acid contained in the long-acting rust conversion agent for metal surface is 10%~13%, and the mass percentage of gallic acid contained in the long-acting rust conversion agent for metal surface is 8%~18%.

[0008] Optionally, the mass percentage of tannic acid contained in the long-acting rust conversion agent for metal surface is 13%~15%, the mass percentage of salicylic acid contained in the long-acting rust conversion agent for metal surface is 11%~12%, and the mass percentage of gallic acid contained in the long-acting rust conversion agent for metal surface is 10%~15%.

[0009] Optionally, the mass percentage of tannic acid contained in the long-acting rust conversion agent for metal surface is 14%, the mass percentage of salicylic acid contained in the long-acting rust conversion agent for metal surface is 11.5%, and the mass percentage of gallic acid contained in the long-acting rust conversion agent for metal surface is 13%.

[0010] Optionally, the carrier oil is at least one of poly-α-olefin oil, polybutene, synthetic cycloalkane, vegetable oil-based polyol ester, and polyether.

[0011] Optionally, the osmotic stabilizer is a mixture of soybean lecithin and Tween-60 in a weight ratio of 2:1.

[0012] Optionally, the sustained-release carrier is a mixture of sepiolite powder and diatomaceous earth in a weight ratio of 2:1.

[0013] Optionally, the sterilizer is a mixture of fluopicolide, pyraclostrobin and a triazole sterilizer in a weight ratio of 1:1:1.

[0014] Optionally, the antioxidant is a mixture of antioxidant 1010 and antioxidant BHT in a weight ratio of 3:1.

[0015] On the other hand, the present invention also provides a method for preparing the long-acting rust conversion agent for metal surface, the method comprising: First, 30% to 50% by weight of carrier oil is added into a reaction kettle, heated to a temperature of 95°C to 120°C, kept warm for 30min to 40min, then cooled to maintain a temperature of 50°C to 70°C, 1% to 4% by weight of an osmotic stabilizer, 6% to 10% by weight of a sustained-release carrier, and 3% to 5% by weight of a sterilizer are added in sequence, stirred for 20min to 30min, 1% to 2% by weight of an antioxidant, 2% to 6% by weight of a thixotropic agent, 10% to 20% by weight of tannic acid, 9% to 15% by weight of salicylic acid, and 6% to 20% by weight of gallic acid are added, stirred for 1h to 1.5h under normal pressure, and then discharged to obtain the long-acting rust conversion agent for metal surface.

[0016] The present invention has the following beneficial technical effects: The invention provides a long-acting rust conversion agent for metal surface, which adopts tannic acid, gallic acid and salicylic acid at the same time. Tannic acid, gallic acid and salicylic acid cooperate with each other to form a firm complex layer with the formed metal oxide or the metal itself through chelation. The synergistic effect of the three corrosion inhibitors of tannic acid, gallic acid and salicylic acid enhances the synergistic migration protection effect, and can form a relatively dense and flat conversion film on the surface of the corroded metal. The formed conversion film can effectively prevent the corrosive medium from penetrating and contacting the metal, is suitable for steel structures, and is particularly suitable for steel structure connection parts. It has good permeability and high rust conversion efficiency, can convert harmful rust into a protective layer that is beneficial to corrosion prevention, and provides effective protection for the metal matrix. The anti-corrosion effect can reach more than 20 years, and frequent maintenance is avoided, resources and manpower and material resources are saved, and significant economic benefits are achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0018] Figure 1 1 is a metallographic diagram of different transformation products of the embodiments of the present invention; Figure 2 Schematic diagram of scanning electron microscopy of different transformation products of the embodiments of the present invention; Figure 3 The Nyquist diagram and Bode diagram of the coating of the bare steel sample with different immersion times according to the embodiment of the present invention are shown; Figure 4 The impedance spectrum equivalent circuit diagram of an embodiment of the present invention; Figure 5The Nyquist diagram and Bode diagram of the rusted steel sample coating at different immersion times according to the embodiment of the present invention are shown; Figure 6 The impedance value comparison between the rusted steel sample coating and the bare steel sample coating in the embodiment of the present invention; Figure 7 This is a salt spray test diagram based on a bare steel sample coating for 1440 h in an embodiment of the present invention; Figure 8 This is a salt spray test diagram based on a rusted steel coating for 1440 h in an embodiment of the present invention; Fig. 9 This is a salt spray test diagram based on a bare steel sample coating for 1440 h in an embodiment of the present invention; Fig.10 This is a salt spray test diagram based on a rusted steel coating for 1440 h according to an embodiment of the present invention. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] In view of the shortcomings of existing rust-proof and rust-converting agents, such as high toxicity, poor construction economy, poor permeability, and general protection effect against microbial corrosion, the embodiments of the present invention provide a long-acting rust conversion agent for metal surfaces, which is suitable for steel structures, especially for steel structure connection parts. It has good permeability and high rust conversion efficiency, and can form a relatively dense and smooth conversion film. The formed conversion film can effectively prevent the corrosive medium from penetrating into and contacting the metal, and can convert harmful rust into a protective layer that is beneficial to corrosion prevention, thereby providing effective protection for the metal substrate. The anti-corrosion effect can reach more than 20 years, eliminating the need for more frequent maintenance, saving resources and manpower and material resources, and having significant economic benefits.

[0021] A long-acting rust conversion agent for metal surface provided by an embodiment of the present invention comprises 30% to 50% by mass of carrier oil, 1% to 4% by mass of osmotic stabilizer, 6% to 10% by mass of sustained-release carrier, 3% to 5% by mass of sterilizer, 1% to 2% by mass of antioxidant, 2% to 6% by mass of thixotropic agent, 10% to 20% by mass of tannic acid, 9% to 15% by mass of salicylic acid, and 6% to 20% by mass of gallic acid, wherein the total mass percentage of tannic acid, salicylic acid and gallic acid contained in the long-acting rust conversion agent for metal surface is 25% to 50%.

[0022] Among them, preferably, the mass percentage of tannic acid contained in the long-acting rust conversion agent for metal surface provided by the embodiment of the present invention is 12% to 16%, the mass percentage of salicylic acid contained in the long-acting rust conversion agent for metal surface is 10% to 13%, and the mass percentage of gallic acid contained in the long-acting rust conversion agent for metal surface is 8% to 18%. Tannic acid, gallic acid and salicylic acid under this mass percentage can cooperate with each other to form a firm complex layer through chelation with the already formed metal oxide or the metal itself, and the three corrosion inhibitors of tannic acid, gallic acid and salicylic acid can better play a synergistic role, enhance the role of synergistic migration protection, and form a relatively dense and smooth conversion film on the surface of the corroded metal, and the formed conversion film can effectively prevent the corrosive medium from penetrating and contacting the metal.

[0023] Furthermore, the mass percentage of tannic acid contained in the long-acting rust conversion agent for metal surface of the embodiment of the present invention is 13%~15%, the mass percentage of salicylic acid contained in the long-acting rust conversion agent for metal surface is 11%~12%, and the mass percentage of gallic acid contained in the long-acting rust conversion agent for metal surface is 10%~15%.

[0024] Rust converters prepared from different acids react differently with rust. Tannic acid contains a large number of hydroxyl and carboxyl groups, which can react with iron ions in the rust layer to form a stable tannic acid iron complex salt; gallic acid contains one carboxyl group and three phenolic hydroxyl groups, of which the phenolic hydroxyl group has a strong chelating ability and can form a complex with iron ions; salicylic acid reacts relatively mildly with rust, and can react chemically with rust at room temperature or high temperature to form a harmless chelate with a certain protective effect. However, due to the difference in acidity, the conversion effect of different acids on the rust layer and the degree of damage to the matrix are different. Strong acidic substances will corrode the metal matrix, and the excess hydrogen produced will also lead to an increase in paint film defects. Therefore, even if a protective layer is formed on the metal surface, it will quickly fail and cannot achieve the purpose of long-term corrosion protection. Weakly acidic substances cannot provide enough anions to react with iron ions, so they cannot form stable chelates to protect the matrix, and the residual rust will continue to expand, causing the metal corrosion to worsen. Tannic acid, gallic acid and salicylic acid are combined to prepare a composite rust conversion agent, which is then applied to rusty steel samples. This can make up for the defects caused by a single acid and give full play to the synergistic advantages of their mutual cooperation.

[0025] The process of the reaction between the rust converter and the rust layer on the metal surface can be divided into the following three stages: first, the acidic substance hydrolyzes to release hydrogen ions; second, the hydrogen ions react with the rust on the metal surface to dissolve it into ferric ions or ferrous ions; and finally, the generated acid radical ions chelate with the generated ionic iron to convert into a stable and harmless organic chelate. Among the three substances, tannic acid, gallic acid and salicylic acid, tannic acid has a stronger acidity and is a medium-strong organic acid, which can easily dissociate water molecules. Therefore, adding tannic acid first can promote the hydrolysis process, and while generating anions, a large amount of hydrogen ions are precipitated (refer to formula (1)), providing a favorable condition for the subsequent reaction with rust. Salicylic acid is slightly soluble in water, but has a high complexing strength with iron ions. In a tannic acid environment, hydrogen ions can react with rust to form ionic iron (see formula (2)). Under this condition, salicylic acid is more likely to complex with free iron ions to form a stable and harmless precipitate. This substance can firmly adhere to the metal surface to form a complex precipitation layer. Therefore, adding an appropriate amount of salicylic acid after adding tannic acid can not only slow down the corrosion rate, but also improve the protection of the metal matrix. Tannic acid can also play a role in this stage. After hydrolysis, under the action of its many polar groups, it can react with iron ions or ferrous ions to form a blue-black complex (see formula (3)). Tannic acid also has the characteristic of absorbing oxygen, which can prevent metal oxidation and improve its passivation ability. Gallic acid is a small molecule polyphenol compound with weaker activity. It can also react with rust when used alone to convert it into stable and harmless compounds, but the process is slow and cannot achieve the purpose of rapid rust removal and cannot inhibit further development of rust. However, it is environmentally friendly and does not easily corrode the metal matrix. Therefore, after adding tannic acid and salicylic acid, adding an appropriate amount of gallic acid can replace part of the organic medium and strong acid, reduce the overall acid strength, achieve rapid conversion of the rust layer, and prevent corrosion to the metal matrix.

[0026] (1) (2) (3) Through a large number of experimental studies, it was found that when the mass percentage of tannic acid contained in the long-acting rust conversion agent for metal surface of the embodiment of the present invention is 14%, the mass percentage of salicylic acid contained in the long-acting rust conversion agent for metal surface is 11.5%, and the mass percentage of gallic acid contained in the long-acting rust conversion agent for metal surface is 13%, the tannic acid, gallic acid and salicylic acid at this mass percentage can cooperate with the already formed metal oxide or the metal itself to form a firm complex layer through chelation, and the three corrosion inhibitors of 14% tannic acid, 11.5% gallic acid and 13% salicylic acid can better play a synergistic role, enhance the synergistic migration protection effect, and form a relatively dense and smooth conversion film on the surface of the corroded metal. The surface cracks of the conversion film formed at this mass percentage are the least and the depth is shallower, and the formed conversion film can better hinder the corrosive medium from penetrating and contacting the metal.

[0027] The carrier oil used in the long-acting rust conversion agent for metal surface of the embodiment of the present invention is at least one of poly-α-olefin oil, polybutene, synthetic cycloalkane, vegetable oil-based polyol ester, and polyether. The osmotic stabilizer is a mixture of soybean lecithin and Tween-60 in a weight ratio of 2:1. The sustained-release carrier is a mixture of sepiolite powder and diatomaceous earth in a weight ratio of 2:1. The sterilizer is a mixture of fluopicolide, pyraclostrobin and triazole sterilizer in a weight ratio of 1:1:1. The antioxidant is a mixture of antioxidant 1010 and antioxidant BHT in a weight ratio of 3:1.

[0028] The long-acting rust conversion agent for metal surface of the embodiment of the present invention is environmentally friendly and non-toxic, has no pollution to the environment, contains no volatile organic matter, and does not contain dangerous goods. There is no harm to construction personnel when they come into contact with the long-acting rust conversion agent for metal surface of the embodiment of the present invention. The tannic acid, gallic acid, salicylic acid, etc. used in the present invention are all materials with no side effects on the environment, and the sterilizers used are all new environmentally friendly sterilizers. In addition, other components are also harmless to the human body and the environment. Even if leakage occurs, it will not cause pollution to the environment or the consequences thereof are predictable or controllable.

[0029] A long-acting rust conversion agent for metal surface according to an embodiment of the present invention has low surface treatment requirements and is suitable for port and terminal facilities, offshore platforms, power plant steel frames, storage tank bottom edge plates, and pipeline valves in the marine industry. Usually, due to the limitations of operating conditions and the like at the construction site, it is difficult for the surface treatment to reach the required level. However, when a long-acting rust conversion agent for metal surface according to an embodiment of the present invention is used, the surface treatment only needs to reach St2.0, and the construction process is flexible and simple, and the construction tolerance is good. In view of the characteristics of the metal structure, a variety of construction methods can be used, including manual smearing, scraping, brushing, glue gun extrusion application, and spraying; in addition, a long-acting rust conversion agent for metal surface according to an embodiment of the present invention can be constructed with water and rust, and the anti-corrosion protective film formed after coating can easily cover the surface of the object to be protected.

[0030] A long-acting rust conversion agent for metal surface according to an embodiment of the present invention has a long-lasting anti-corrosion protection function, the anti-corrosion layer has strong adhesion and good dense isolation, outstanding synergistic protection effect, good permeability and strong chelating rust inhibition ability. First, a long-acting rust conversion agent for metal surface according to an embodiment of the present invention uses tannic acid, gallic acid and salicylic acid, which can form a firm complex layer with the already formed metal oxide or the metal itself through chelation. The three corrosion inhibitors of tannic acid, gallic acid and salicylic acid cooperate with each other to play a synergistic role, thereby enhancing the synergistic migration protection effect; secondly, a long-acting rust conversion agent for metal surface according to an embodiment of the present invention uses two antioxidants to work synergistically, which can effectively prevent the acidification and oxidative deterioration of the anti-corrosion layer for a long time, thereby ensuring the long-term effectiveness of the anti-corrosion effect of the anti-corrosion layer. A long-acting rust conversion agent for metal surface in an embodiment of the present invention adopts a combination of three bactericides, namely, fluopicolide, pyraclostrobin and triazoles, which can effectively inhibit or kill microorganisms that are prone to growth, such as sulfate-reducing bacteria, sulfur-oxidizing bacteria, saprophytes, iron bacteria and fungi, thereby preventing corrosion damage caused by the failure of anti-corrosion materials due to the secretion of intermediate products and / or final products of microbial cell metabolism and exoenzymes.

[0031] Based on the same inventive concept, the present invention also provides a method for preparing the above-mentioned long-acting rust conversion agent for metal surface, comprising: First, 30% to 50% by weight of carrier oil is added into a reaction kettle, heated to a temperature of 95°C to 120°C, kept warm for 30min to 40min, then cooled to maintain a temperature of 50°C to 70°C, 1% to 4% by weight of an osmotic stabilizer, 6% to 10% by weight of a sustained-release carrier, and 3% to 5% by weight of a sterilizer are added in sequence, stirred for 20min to 30min, 1% to 2% by weight of an antioxidant, 2% to 6% by weight of a thixotropic agent, 10% to 20% by weight of tannic acid, 9% to 15% by weight of salicylic acid, and 6% to 20% by weight of gallic acid are added, stirred for 1h to 1.5h under normal pressure, and then discharged to obtain the long-acting rust conversion agent for metal surface.

[0032] In the embodiment of the present invention, Q235 low-carbon steel, which is commonly used in engineering projects, is selected as a test substrate for metal surface anti-rust conversion. A rust layer with good bonding strength is prepared through continuous salt spray exposure. Different rust conversion agents are added to epoxy resin to prepare a coating, which is then applied to a uniformly treated rusted steel sample and a bare steel sample, respectively.

[0033] In order to make the rust adhere better to the substrate surface, the Q235 low carbon steel working electrode (10 mm × 10 mm × 10 mm) and the Q235 low carbon steel sample (150 mm × 75 mm × 1 mm) were degreased and dusted, and polished step by step with 400 mesh, 800 mesh, and 1000 mesh sandpaper respectively. Finally, the surface was wiped with anhydrous ethanol to clean it, and then placed in a salt spray box for accelerated corrosion for 72 h. The steel surface was completely attached with a rust layer, and it was taken out and dried naturally in the air. The surface rust was removed with sandpaper and a soft brush, and the residual NaCl in the rust layer was rinsed with deionized water. The oven temperature was set to 35 ° C, and the rust layer of (37 ± 4.2) μm was obtained after drying for 24 h.

[0034] Use an electronic balance to weigh a certain amount of epoxy resin and add it to a laboratory disperser. Add active diluent and disperse evenly at a speed of 1500 r / min for 5 minutes. Then mix the filler, rust converter, dispersant and epoxy resin. The amount of rust converter added is 4wt.%, and the ratio of the volume fraction of pigments and fillers to the volume fraction of critical pigments and fillers is fixed at 0.7. Adjust the speed to 2000 r / min and stir for 5 minutes, then add the additive and continue stirring for 1 hour to make it evenly dispersed. After cooling, put it into a bottle and label it for later use.

[0035] The long-acting rust converter for metal surface of the embodiment of the present invention and the rust converter of the comparative example were respectively applied to the treated substrate surface by brushing, (480±30) μm, dried at room temperature for 7 days, and then completely cured for basic performance test, AC impedance test and neutral salt spray test of the coating. Among them, the comparative examples are rust converters prepared by using tannic acid and salicylic acid as corrosion inhibitors, tannic acid as corrosion inhibitor, salicylic acid as corrosion inhibitor, and gallic acid as corrosion inhibitor. The product morphology of the basic performance test is as follows Figure 1 As shown, Figure 1 The image is obtained by observing the surface of the rust layer after being converted by different rust conversion agents using a metallographic microscope, with a magnification of 400 times. Figure 1 a is rusty steel; Figure 1 b is a composite acid system of tannic acid, gallic acid and salicylic acid; Figure 1 c is a composite acid system of tannic acid and salicylic acid; Figure 1 d is tannic acid; Figure 1 e is salicylic acid; Figure 1 f is gallic acid. Figure 1 It can be seen that the rust layer surface after being treated with different rust conversion agents presents different states. Among them, the tannic acid, gallic acid and salicylic acid composite acid system ( Figure 1 b) has the best conversion effect. Figure 1 Compared with the rusted steel sample shown in a, the original rust morphology on the surface was transformed to form a relatively complete and dense conversion film. Tannic acid and salicylic acid composite acid system ( Figure 1 c) The rust layer also undergoes transformation and forms a conversion film on the surface, but there are some holes and small cracks on the surface of the film. Figure 1 d) Salicylic acid ( Figure 1 e) and gallic acid ( Figure 1 f) It also has a certain transformation effect. You can see that the rust on the original rust layer disappears, but the surface after transformation is rough and uneven, which means that the rust layer transformation is incomplete and there may be residual rust.

[0036] The film formed before and after the rust layer transformation was characterized by scanning electron microscopy. Figure 2 As shown, Figure 2 a is rusty steel; Figure 2 b is gallic acid; Figure 2 c is salicylic acid; Figure 2 d is tannic acid; Figure 2 e is a composite acid system of tannic acid and salicylic acid; Figure 2 f is a composite acid system of tannic acid, gallic acid and salicylic acid. Figure 2As can be seen in a, the surface of the unconverted rusted steel sample presents blocky and granular morphology, and the rust layer is loose with a large number of pores, which will destroy the structure of the metal matrix and affect its performance. After the rusted steel sample is treated with different rust conversion agents, it can be found that the surface morphology has obvious changes. Among them, the rust layer on the sample is treated with gallic acid ( Figure 2 b) and salicylic acid ( Figure 2 c), the block structure basically disappeared, forming a relatively dense conversion film, but there were still obvious cracks on the surface of the film, and some granular products were distributed, especially the film obtained by salicylic acid conversion was rougher, because the rust was not completely converted and still remained on the surface of the film. Figure 2 d), the morphology of the rusted steel samples after conversion has been greatly improved. Although there are still cracks on the surface, the loose rust has completely disappeared and has been converted into a dense and smooth conversion film, which has a certain protective effect on the metal substrate. However, the film layer after conversion by tannic acid has relatively more cracks and the gap width is larger; after conversion by tannic acid and salicylic acid composite acid system ( Figure 2 After treatment with tannic acid, gallic acid, and salicylic acid composite acid system ( Figure 2 f) The conversion film formed after treatment is slightly less smooth and flat, but has fewer and shallower cracks on the surface, with no metal matrix exposed, which can effectively inhibit the penetration of corrosive media.

[0037] Based on the analysis of the AC impedance results of the bare steel sample coating, Figure 3 As shown, the equivalent circuit diagram of the impedance spectrum based on the bare steel sample coating is shown in Figure 4 As shown, Figure 4 Where Rs represents the solution resistance, Qc represents the coating capacitance, Rp represents the coating resistance, Rc is the micropore resistance of the electrolyte penetrating coating, Qdl and Rt represent the double layer capacitance and charge transfer resistance at the interface between metal and coating, respectively. Figure 4 The equivalent circuit diagram with only one time constant is fitted as shown in a. As the immersion time increases, the corrosive medium penetrates the coating and contacts the metal, and corrosion occurs. The impedance arc diffusion phenomenon becomes obvious from the Nyquist diagram. At this time, according to Figure 4 The equivalent circuit with two time constants shown in b is fitted.

[0038] refer to Figure 3 As shown in the figure, the larger the impedance arc radius of the Nyquist diagram, the better the coating's ability to block corrosive media. Similarly, the higher the impedance modulus value in the low-frequency region of the Bode diagram, the stronger the coating's anti-corrosion ability. Figure 3As can be seen from Table 1, during the entire immersion process, the impedance arc radius of each coating in the Nyquist diagram gradually decreases, the impedance value decreases, and the low-frequency 0.01 Hz impedance modulus in the Bode diagram also shows a downward trend. This is because as the immersion time increases, the corrosive medium gradually penetrates into the coating, weakening its shielding ability, thereby reducing the coating's ability to protect the metal substrate. Analysis shows that compared with 24 h ( Fig.10 Compared with the case of immersion for 360 h ( Figure 3 b) The impedance values ​​of each coating decreased, but were all higher than 1010Ω·cm 2 This indicates that the coating containing the rust conversion agent has a certain anti-corrosion ability and can effectively inhibit the penetration of corrosive media. After immersion for 1440 hours, Figure 3 As shown in e, the impedance modulus of the coating prepared by gallic acid at 0.01 Hz is lower than 108 Ω·cm 2 , and the impedance arc diffuses in the low-frequency region, indicating that the corrosive medium has penetrated the coating and reacted with the metal matrix to cause corrosion, causing the coating to gradually lose its ability to protect the metal matrix. The impedance value of the coating prepared by tannic acid, salicylic acid and its composite acid system is still higher than 1010Ω·cm 2 , and the impedance arc radius and low-frequency impedance modulus of these three coatings are significantly higher than those of other coatings during the entire immersion period.

[0039] Table 1 AC impedance fitting results based on different immersion time of bare steel sample coating

[0040] Based on the AC impedance analysis of the rusted steel sample coating, Figure 5 As shown, the equivalent circuit diagram of the impedance spectrum based on the rusted steel sample coating is as follows Figure 5 As shown, from Figure 5 It can be seen from Table 2 that during the entire immersion process, the impedance arcs in the Nyquist diagrams of all coatings gradually become complete, indicating that the failure modes of each coating are basically the same, and the corrosive medium gradually penetrates into the coating as the immersion time increases. Figure 5 It can be seen from a that after immersion for 24 h, the impedance arc radius of each coating in the Nyquist diagram is relatively large, and the low-frequency impedance modulus values ​​of the Bode diagram are all higher than 1010Ω·cm 2 , at this time, each coating has a good shielding effect. After immersion for 360 hours, Figure 5 As shown in b, the impedance arc radius in the Nyquist diagram has decreased, and the impedance modulus in the Bode diagram has also begun to decrease, but overall there is little difference compared to the state at 24 h, and it is still in the early stage of immersion. Figure 5c), the Nyquist diagram and the Bode diagram have obvious changes. Combined with Table 2, it can be seen that the impedance values ​​of the sample coatings prepared by gallic acid and salicylic acid are greatly reduced, indicating that the metal substrate is corroded by corrosion products. The reason is that the porosity of these two coatings is large and the shielding ability is poor, which leads to the penetration of corrosive media, resulting in a rapid decrease in electrochemical impedance. Continue to immerse the coating, it can be found that the radius of the Nyquist impedance arc is further reduced, and a platform appears in the low-frequency region of the impedance modulus curve of the Bode diagram, indicating that the corrosive medium has penetrated into each coating and the shielding ability of the coating has decreased. When the immersion time reaches 1440 h, each coating basically forms a complete impedance arc. The coating prepared by the composite acid system of tannic acid, gallic acid, and salicylic acid decreases relatively slowly, indicating that the conversion film of the composite acid system coating plays a barrier role, slowing down the process of the electrolyte solution penetrating into the coating and limiting the corrosion behavior.

[0041] Table 2 AC impedance fitting results based on different immersion time of rusted steel sample coating

[0042] The changes of the AC impedance fitting results of different coatings and different samples with immersion time are plotted as a bar graph, such as Figure 6 As shown, Figure 6 a is a composite acid system of tannic acid, salicylic acid and gallic acid; Figure 6 b is a composite acid system of tannic acid and salicylic acid; Figure 6 c is tannic acid; Figure 6 d is salicylic acid; Figure 6 e is gallic acid. Figure 6 It can be seen that the impedance values ​​of all coatings, whether based on bare steel or rusted steel, decrease with the increase of immersion time, but the impedance value of the rusted steel coating is always higher than that of the bare steel, especially the tannic acid, salicylic acid, gallic acid composite acid system ( Figure 6 The coating prepared by (as shown in a) has an impedance value improvement rate of about 30%. This is because the rust conversion agent in the coating plays a role and reacts with the rust layer on the sample to form a conversion film, which inhibits the penetration of corrosive media and strengthens the protection of the metal substrate.

[0043] Figure 7 and Figure 8 The results of the coatings prepared by different rust conversion agents on bare steel samples and rusted steel samples after 1440 h of neutral salt spray test are shown in Figure 2. Figure 7 a and Figure 8 a is a composite acid system of tannic acid, salicylic acid and gallic acid; Figure 7 b and Figure 8 b is a composite acid system of tannic acid and salicylic acid; Figure 7 c and Figure 8c is tannic acid; Figure 7 d and Figure 8 d is salicylic acid; Figure 7 e and Figure 8 e is gallic acid. Figure 7 and Figure 8 It can be seen that different rust converters have different corrosion degrees, and the same converter coating applied on samples in different states will also have different corrosion conditions. Figure 7 It can be seen that the coating prepared by the composite acid system of tannic acid, salicylic acid and gallic acid has a lighter overall corrosion degree than other coatings. There is almost no change in the scratch-free area of ​​the upper half of the sample, and only a small amount of rust is generated in the scratched area of ​​the lower half, indicating that the coating can play a role in shielding the corrosive medium. Figure 8 The corrosion of the rusted steel sample coating is lighter, and the degree of corrosion in the scratched area is less than that of the bare steel sample, achieving the effect of converting the rust layer to protect the metal substrate; the corrosion of the coating prepared by salicylic acid and gallic acid is more serious, especially for the rusted steel sample. Not only is the bulge phenomenon obvious at the scratched area, but also bubbles appear in the upper area without scratches, which creates a gap between the coating and the metal substrate. The reason for this is that on the one hand, the barrier ability of the coating itself is poor, and the corrosive medium easily penetrates the coating and contacts the metal substrate, producing a large amount of corrosion products, resulting in volume expansion. On the other hand, the coating cannot convert the rust on the sample well, causing it to spread and diffuse, which greatly reduces the impedance of the coating. The results of the salt spray test are consistent with the results of the AC impedance. The fewer the bubbling phenomenon and corrosion products of the sample coating, the higher the impedance value of the coating, and the better the anti-corrosion effect.

[0044] Fig. 9 and Fig.10 The results of neutral salt spray tests on bare steel samples and rusted steel samples were performed on coatings prepared by rust conversion agents of composite acid systems of tannic acid, salicylic acid and gallic acid with different weight ratios. Fig. 9 a and Fig.10 a is tannic acid: salicylic acid: gallic acid = 3:2:1; Fig. 9 b and Fig.10 b is tannic acid: salicylic acid: gallic acid = 2:1:1; Fig. 9 c and Fig.10 c is tannic acid: salicylic acid: gallic acid = 1:2:1; Fig. 9 d and Fig.10 d is tannic acid: salicylic acid: gallic acid = 1:1:1; Fig. 9 e and Fig.10e is tannic acid: salicylic acid: gallic acid = 1: 1: 2. It can be seen that the coatings are corroded to varying degrees after 1440 h of testing in the salt spray test chamber, wherein the metal surface long-acting rust converter of the embodiment of the present invention with a mass percentage ratio of tannic acid: salicylic acid: gallic acid = 1: 1: 2 in the composite acid system is relatively severely corroded, with more rust products near the scratches, and bubbling phenomenon especially in the coating of the bare steel sample. The surface state of the coatings with the remaining additions is relatively good, especially the coating with a ratio of tannic acid: salicylic acid: gallic acid = 3: 2: 1 in the composite acid system, which has almost no trace of corrosion.

[0045] Through the above product morphology and electrochemical performance analysis, the following conclusions are drawn: (1) In the comparative analysis of the rust conversion system, it can be seen that the rust on the surface of the sample after conversion by the composite acid system of tannic acid, gallic acid and salicylic acid disappears, and a relatively dense and smooth conversion film is formed. Although there are some small cracks, no metal matrix is ​​exposed, indicating that the composite acid system rust converter reacts with the rust layer on the surface of the sample and has good rust conversion performance. The formed conversion film can effectively prevent the corrosive medium from penetrating and contacting the metal.

[0046] (2) Through the AC impedance test and the neutral salt spray test, it can be found that the coating with the composite acid system of tannic acid, gallic acid and salicylic acid has a certain ability to remove rust from rusted steel samples, and can also play an anti-corrosion role on bare steel samples. After 1440 hours of immersion in 3.5wt.% NaCl solution, the coating on the rusted steel sample and the bare steel sample can still maintain a resistance of 1010Ω·cm 2 The above values ​​are higher than those of the coating on the rusted steel sample, and the impedance value of the coating on the bare steel sample is higher than that of the coating on the bare steel sample; after 1440 h of neutral salt spray test, the coating prepared by the composite acid system of tannic acid, gallic acid and salicylic acid (tannic acid: salicylic acid: gallic acid = 3:2:1) has only a small amount of rust at the scratches, without bubbling, shedding, etc. This shows that the coating prepared by the rust converter of the embodiment of the present invention can convert harmful rust into a protective layer that is beneficial to corrosion protection, providing effective protection for the metal substrate.

[0047] The invention provides a long-acting rust conversion agent for metal surface, which adopts tannic acid, gallic acid and salicylic acid at the same time. Tannic acid, gallic acid and salicylic acid cooperate with each other to form a firm complex layer with the formed metal oxide or the metal itself through chelation. The synergistic effect of the three corrosion inhibitors of tannic acid, gallic acid and salicylic acid enhances the synergistic migration protection effect, and can form a relatively dense and flat conversion film on the surface of the corroded metal. The formed conversion film can effectively prevent the corrosive medium from penetrating and contacting the metal, is suitable for steel structures, and is particularly suitable for steel structure connection parts. It has good permeability and high rust conversion efficiency, can convert harmful rust into a protective layer that is beneficial to corrosion prevention, and provides effective protection for the metal matrix. The anti-corrosion effect can reach more than 20 years, and frequent maintenance is avoided, resources and manpower and material resources are saved, and significant economic benefits are achieved.

[0048] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A long-acting rust conversion agent for metal surface, characterized in that: The long-acting rust conversion agent for metal surface comprises 30% to 50% by mass of carrier oil, 1% to 4% by mass of osmotic stabilizer, 6% to 10% by mass of slow-release carrier, 3% to 5% by mass of sterilizer, 1% to 2% by mass of antioxidant, 2% to 6% by mass of thixotropic agent, 10% to 20% by mass of tannic acid, 9% to 15% by mass of salicylic acid, and 6% to 20% by mass of gallic acid, wherein the total mass percentage of tannic acid, salicylic acid and gallic acid contained in the long-acting rust conversion agent for metal surface is 25% to 50%.

2. The long-acting rust conversion agent for metal surface according to claim 1, characterized in that: The mass percentage of tannic acid contained in the long-acting rust conversion agent for metal surface is 12% to 16%, the mass percentage of salicylic acid contained in the long-acting rust conversion agent for metal surface is 10% to 13%, and the mass percentage of gallic acid contained in the long-acting rust conversion agent for metal surface is 8% to 18%.

3. The long-acting rust conversion agent for metal surface according to claim 1, characterized in that: The mass percentage of tannic acid contained in the long-acting rust conversion agent for metal surface is 13% to 15%, the mass percentage of salicylic acid contained in the long-acting rust conversion agent for metal surface is 11% to 12%, and the mass percentage of gallic acid contained in the long-acting rust conversion agent for metal surface is 10% to 15%.

4. The long-acting rust conversion agent for metal surface according to claim 1, characterized in that: The mass percentage of tannic acid contained in the long-acting rust conversion agent for metal surface is 14%, the mass percentage of salicylic acid contained in the long-acting rust conversion agent for metal surface is 11.5%, and the mass percentage of gallic acid contained in the long-acting rust conversion agent for metal surface is 13%.

5. The long-acting rust conversion agent for metal surface according to any one of claims 1 to 4, characterized in that: The carrier oil is at least one of poly-α-olefin oil, polybutene, synthetic cycloalkane, vegetable oil-based polyol ester, and polyether.

6. The long-acting rust conversion agent for metal surface according to any one of claims 1 to 4, characterized in that: The osmotic stabilizer is a mixture of soybean lecithin and Tween-60 in a weight ratio of 2:

1.

7. The long-acting rust conversion agent for metal surface according to any one of claims 1 to 4, characterized in that: The sustained-release carrier is a mixture of sepiolite powder and diatomaceous earth in a weight ratio of 2:

1.

8. The long-acting rust conversion agent for metal surface according to any one of claims 1 to 4, characterized in that: The sterilizer is a mixture of fluopicolide, pyraclostrobin and a triazole sterilizer in a weight ratio of 1:1:

1.

9. The long-acting rust conversion agent for metal surface according to any one of claims 1 to 4, characterized in that: The antioxidant is a mixture of antioxidant 1010 and antioxidant BHT in a weight ratio of 3:

1.

10. A method for preparing the long-acting rust conversion agent for metal surface according to any one of claims 1 to 4, characterized in that: The method comprises: First, 30% to 50% by weight of carrier oil is added into a reaction kettle, heated to a temperature of 95°C to 120°C, kept warm for 30min to 40min, then cooled to maintain a temperature of 50°C to 70°C, 1% to 4% by weight of an osmotic stabilizer, 6% to 10% by weight of a sustained-release carrier, and 3% to 5% by weight of a sterilizer are added in sequence, stirred for 20min to 30min, 1% to 2% by weight of an antioxidant, 2% to 6% by weight of a thixotropic agent, 10% to 20% by weight of tannic acid, 9% to 15% by weight of salicylic acid, and 6% to 20% by weight of gallic acid are added, stirred for 1h to 1.5h under normal pressure, and then discharged to obtain the long-acting rust conversion agent for metal surface.

Citation Information

Cited By

  • A weathering steel rust layer yellow coloring treatment agent and a method for using the same

    CN122522237A

  • A weathering steel rust layer purple coloring treatment agent and a method of using the same

    CN122628597A

  • A weathering steel rust layer orange coloring treatment agent and a method for using the same

    CN122648925A

  • A weathering steel rust layer black coloring treatment agent and a method for using the same

    CN122772497A